A dihydroxy-pentamethoxyflavone from Gardenia obtusifolia suppresses proliferation and promotes apoptosis of tumor cells through modulation of multiple cell signaling pathways - Phromnoi K. (2014)
We sought to determine the molecular basis for the anticancer activities of 5,3′-dihydroxy-3,6,7,8,4′-penta-methoxyflavone (DH-PMF), isolated from Gardenia obtusifolia traditionally used in Thailand for a variety of ailments. As little as 1 μM DH-PMF inhibited the proliferation of prostate, colon, kidney, lung, head and neck, pancreas, breast, leukemia, and myeloma cancer cell lines. DH-PMF also suppressed the colony-forming ability of tumor cells, with 50% inhibition occurring at a dose less than 10 nM. DH-PMF induced G2/M and subG1 cell cycle arrest, increased the levels of p21WAF1/CIP1 and p27KIP1, and reduced the expression of cyclin D1, CDC2, and c-MYC. Furthermore, DH-PMF inhibited AKT and glycogen synthase kinase 3 beta (GSK3β) activation, reduced cell survival proteins, and induced apoptosis, as indicated by annexin V staining, TUNEL assay, and activation of caspase-8, -9 and -3. Overall, our results demonstrate that DH-PMF induces suppression of cell proliferation through modulation of AKT-GSK3β pathways and induction of cyclin-dependent kinase (CDK) inhibitors.